2010
DOI: 10.1590/s1413-35552010000300008
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação eletromiográfica e ressonância magnética do joelho de indivíduos com síndrome da dor femoropatelar

Abstract: Objectives: To analyze the electrical activity of the vastus medialis obliquus (VMO), vastus lateralis longus (VLL) and vastus lateralis obliquus (VLO) muscles of individuals with patellofemoral pain syndrome (PFPS) during maximum voluntary isometric contraction (MVIC) of lower leg extension with the knee at 30°; to assess pain using a visual analogue scale (VAS); and to assess patellar positioning using magnetic resonance imaging (MRI). Methods: Twelve women with PFPS and 12 clinically normal women were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Por outro lado, estes resultados diferem dos encontrados na literatura por RIBEIRO et al, (2010), MARIANI e CARUSO (1979) e BOUCHER et al, (1992) que também investigaram a relação da atividade EMG entre os músculos VMO e VL, ambos verificando uma diminuição na atividade do VMO no grupo com SDPF em relação ao VL. Entretanto, estes autores avaliaram os sujeitos com o joelho posicionado nos últimos 30° de extensão, enquanto a avaliação eletromiográfica realizada no presente estudo foi obtida com o joelho em 180° e 120°d e ângulo tíbio-femoral, ou seja, a 0° e 60° de flexão.…”
Section: Discussionunclassified
“…Por outro lado, estes resultados diferem dos encontrados na literatura por RIBEIRO et al, (2010), MARIANI e CARUSO (1979) e BOUCHER et al, (1992) que também investigaram a relação da atividade EMG entre os músculos VMO e VL, ambos verificando uma diminuição na atividade do VMO no grupo com SDPF em relação ao VL. Entretanto, estes autores avaliaram os sujeitos com o joelho posicionado nos últimos 30° de extensão, enquanto a avaliação eletromiográfica realizada no presente estudo foi obtida com o joelho em 180° e 120°d e ângulo tíbio-femoral, ou seja, a 0° e 60° de flexão.…”
Section: Discussionunclassified
“…Stensdotter et al 23 reported that an exercise of isometric knee extension at 30° yields greater activation of the VM and Ribeiro et al 24 reassures this finding. The study of Santos et al…”
mentioning
confidence: 90%
“…"a" represents significant difference of AG and "b" represents significant difference of AGAD (p ≤ 0.05). The extension exercise at 30° is also a guideline for rehabilitation and prevention of PFPS by Ribeiro et al 24 for yielding considerable activation of VM. Gramani-Say et al 21 agree by suggesting that the VM function in the dynamic stabilization of the knee joint is more effective in flexion angles from 0° to 30°.…”
mentioning
confidence: 99%
See 2 more Smart Citations